Ibrutinib enhances the bias of T cell responses towards staphylococcal superantigens sustaining inflammation in chronic lymphocytic leukaemia - Tantoush, Fisal; Allsup, David; Naylor-Adamson, Leigh; Voncken, Frank; Caserta, Stefano (Frontiers in Immunology, 2025)
Chronic lymphocytic leukaemia (CLL) is an uncurable haematological malignancy and is associated with significant infection morbidity. Bruton’s tyrosine-kinase inhibitors (e.g., ibrutinib) have improved disease outcomes, but severe infections and poor immunization responses afflict patients. Recently, carriage of the endemic Staphylococcus aureus (SA) was associated with lymphocytosis and decreased survival in CLL patients. We then hypothesized that exposure to staphylococcal superantigens (SAgs), known to promote hyper-inflammatory responses, impairs immunity and increases severe infection risk in CLL patients. Herein, we evaluate the reactivity of T cells and CLL cells to SA SAgs, in cultures derived from ibrutinib-treated and untreated CLL patients. We found that ibrutinib-treated patients had less naive CD8+ T cells (p=0.0348), more checkpoint receptor (TIM-3) expression in memory T cells (p<0.0001), and lower IFNγ/cytokine responses in patient T cells (p≤0.0298). Exposure to SA SAg further increased the accumulation of memory T cells with an exhaustion-phenotype, preferentially in cultures derived from ibrutinib-treated patients (p≤0.0350). Nevertheless, staphylococcal SAgs could not induce regulatory T cells from CLL patients inasmuch as healthy donors (p≤0.0461) and this was associated with accumulation of inflammatory T cells. Significantly, SAg-exposure enhanced inflammatory activation of CLL tumour cells, which acquired CD38, CD40, CD86, while downregulating CD27 (p≤0.005), even in cultures from ibrutinib-treated CLL patients. Thus, we suggest that environmental SAg-exposure promotes the accumulation of pseudo-exhausted T cells, which induce/sustain tumour cell activation, not counteracted by ibrutinib. Our study critically helps understand the chronic inflammatory milieu in CLL patients, with implications for infection morbidity, disease aetiology and future interventions.